Structural and electronic properties of realistic two-dimensional amorphous topological insulators. (25th February 2021) - Focassio, Bruno; Schleder, Gabriel R; Costa, Marcio; Fazzio, Adalberto; Lewenkopf , Caio
Abstract: We investigate the structure and electronic spectra properties of two-dimensional amorphous bismuthene structures and show that these systems are topological insulators. We employ a realistic modeling of amorphous geometries together with density functional theory for electronic structure calculations. We investigate the system topological properties throughout the amorphization process and find that the robustness of the topological phase is associated with the spin–orbit coupling strength and size of the pristine topological gap. Using recursive non-equilibrium Green's function, we study the electronic transport properties of nanoribbons devices with lengths comparable to experimentally synthesized materials. We find a 2 e 2 / h conductance plateau within the topological gap and an onset of Anderson localization at the trivial insulator phase.